Effect of dipyrone, L-NAME and L-arginine on endotoxin-induced rat paw edema - Fracasso, J. F.; NunesdeSouza, R. L.; Teixeira, C. E.; Castro, R. C.; Lepera, EZP; Silva, RFP (Associação Brasileira de Divulgação Científica (ABRADIC), 1996)
Paw edema was induced in male Wistar rats (200-250 g) by intraplantar (ipl) administration of 2.5 mu g endotoxin (Etx). Etx, like carrageenin, produced two distinct edema formation phases, an early phase (75 min) followed by a late phase (7 h). We showed that the edema formation in the early phase was antagonized by dipyrone (80 mg/kg, ip) and indomethacin (1 mg/kg, ip) by 52% and 55%, respectively, and that the late phase was resistant to these drugs. These results suggest that in the early phase prostaglandins appear to be involved in the process. However, the activation of the kinin cascade leading to the release of other mediators may be involved in the increase of edema in the late phase. To test this hypothesis, we investigated whether the release of nitric oxide (NO) is involved in the mechanism of endotoxin-induced rat paw edema during the late phase, using N omega-nitro-L-arginine methyl ester (L-NAME) (50 mu g, ipl) as inhibitor of NO synthase and L-arginine (1 mg, ipl) as substrate of NO synthase. The paw edema induced by Etx was inhibited by L-NAME by 56% and increased by L-arginine by 81%. Furthermore, L-arginine given in combination with L-NAME completely reversed the inhibition of Etx-induced edema produced by L-NAME. These results support the hypothesis that in the late phase NO production is associated with the edema evoked by Etx.
Keywords: endotoxin; dipyrone; L-NAME; paw edema; nitric oxide (NO)